Influence of Nano Boron Carbide Reinforcement on Wear Behavior of ADC 12 and Al 7075 MMC - Ranjan Das, Manas; Ranjan Das, Satya; Pattanaik, Priyabrata (International Journal of Psychosocial Rehabilitation, 2025)
The metal matrix aluminum composites are of great interest to researchers in metal industries; this is a result of the light weight of aluminum & extra properties of reinforcement. This study targets to manufacture aluminum 7075 and ADC 12 – boron carbide composite concentrated with various percentages of B4C. Both composites were added with false size B4C nanoparticles and wear properties were compared. The experimental study is done is with a Pin-on-Disc method with different loads applied, sliding velocity and slow sliding distance. This analysis can be used to replace the monolithic aluminum components which have high wear with the Matrix Metal Aluminum Composite with superior properties